2020
DOI: 10.18231/j.ijoas.2020.010
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of Ear, Nose and Throat manifestations in head injury cases at a tertiary care hospital

Abstract: The rapid increase in the population and Road traffic accidents led to rise in the number of head injury cases. Most of the cases reporting to the tertiary care hospitals present with injuries to ear, nose and throat. these injuries need to be addressed by ENT surgeons in addition general surgeons and neuro surgeons. A prospective study was done by us at tertiary care centre to assess the ear, nose and throat manifestations in head injury cases. The study was carried over a period of ten years and 100 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In our series there were eight ( 16,17 In our series, there was no any statistically significant difference in the outcome in Terms of GOS and mean hospital stay in between patients with ENT manifestations and those without ENT manifestations.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In our series there were eight ( 16,17 In our series, there was no any statistically significant difference in the outcome in Terms of GOS and mean hospital stay in between patients with ENT manifestations and those without ENT manifestations.…”
Section: Discussionmentioning
confidence: 41%
“…Hearing loss were evaluated in ENT OPD with PTA and almost all of them had conductive hearing loss which had spontaneous resolution. Facial Palsy was reported in 6.6% -10% by other investigators [16][17]. While one patient in the series ofJarandikar AA et al required facial nerve decompression while Patil S et al reported spontaneous resolution.…”
mentioning
confidence: 94%
“…Brain damage may or may not be a part of this. With the increasing urbanization and industrialization in the developing countries and lack of safety precautions and traffic rules adherence the frequency of head injuries has also increased [1][2] . The varying degrees of physical and functional damage are associated with the ENT manifestation.…”
Section: Introductionmentioning
confidence: 99%